Assessment of Advanced Filtration Systems for Sustainable Drinking Water Purification - Khadse, Sneha; Jasuja, N. D. (Journal of Neonatal Surgery, 2025)
Modern water filtration technology appeared because society needed solutions for worldwide challenges regarding water supply that protects both sustainability and public health. Water treatment approaches today demonstrate multiple limitations which enables the requirement for new solutions because they fail to handle future pollution risks and keep energy usage efficient. This research looks into how nanotechnology technology should alter the functions of water purification systems. Nanomaterials function through their properties including nano adsorbents and nanomembranes and photocatalysts to obtain efficient heavy metal removal and organic compound and pathogen removal from water. Through the implementation of hybrid nanofiltration and reverse osmosis filtration water quality significantly improves while micro-pollutants effectively remove from the water stream. This paper demonstrates how water treatment processes gain enhancement through specific nanoscale characteristics of nanotechnology specifically in disinfection and adsorption and catalysis methods. The research demonstrates how nanomaterials reduce operational energy needs by obtaining better environmental outcomes for large-scale water treatment systems at reasonable costs. More widespread use of nanotechnology systems depends on solving existing challenges regarding system scalability together with cost efficiency issues while addressing environmental issues. The global water access expansion depends on extensive research that maximizes nanotechnology water purification methods to ensure sustainability.